Effects of air-assisted solar drying on poplar lumber drying processes in sub frigid zone regions. Issue 16 (12th December 2022) - Chi, Xiang; Tang, Sai; Du, Xinyuan; Song, Xiaoxue; Qi, Zhengyu; Yan, Xu; Han, Gangping; Shi, Sheldon Q.; Cheng, Wanli
Abstract: To study the feasibility and applicability of air energy assisted solar drying under low radiation value conditions in sub frigid zone regions, an intermittent air energy assisted solar heating (IAEASH) process was developed using the 100 Degrees Celsius Test Method and the controlled variable method. Experiments were conducted on two drying processes, namely, continuous air energy assisted solar heating (CAEASH) and IAEASH, using an air energy assisted solar drying system. Poplar sawn lumbers were used in the experiments. The drying processes of both CAEASH and IAEASH methods were compared and analyzed. Results showed that the effective heating time for IAEASH was reduced by 21 h compared to CAEASH, with an average of 23.9%/h increase in drying rate during effective heating. The average radial and tangential dry shrinkage strains of IAEASH during drying ranged from −0.011 to 0.048 and from 0.004 to 0.039 respectively, which were better than the experimental results of CAEASH, and reduced the shrinking of poplar lumber. The IAEASH dried lumber showed neater arrangement between cells. The power consumption of IAEASH was 314.5 kWh, which represented a 50.7% improvement in energy efficiency compared to CAEASH. In summary, the developed IAEASH process is feasible for application in sub frigid zone regions.